Visual Surveillance for Hajj and Umrah: A Review - Yasir Salih Ali; Mohammed Talal Simsim (Institute of Advanced Engineering and Science, 2014)
This paper presents advances on crowd management research with specific interest on high density crowds such as Hajj and Umrah crowds. In the past few years, there has been increasing interest in pursuing video analytics and visual surveillance to improve the security and safety of pilgrimages during their stay in Mecca. Despite the fact that visual surveillance research has matured significantly in the rest of the world and had been implemented in many scenarios, research on visual surveillance for Hajj and Umrah application still remains at its early stages and there are many issues that need to be addressed in future research. This is mainly because Hajj is a very unique event that shows the clustering of millions of people in small area where most advanced image processing and computer vision algorithms fail to generate accurate analysis of the image content. There is a strong need to develop new algorithms specifically tailored for Hajj and Umrah applications. This review aims to give attentions to these interesting future research areas based on analysis of current visual surveillance research. The review also pinpoint to pioneer techniques on visual surveillance in general that can be customized to Hajj and Umrah applications.